2018
DOI: 10.1021/acschemneuro.8b00346
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Allosteric Mechanism of Setmelanotide (RM-493) as a Potent and First-in-Class Melanocortin-4 Receptor (MC4R) Agonist To Treat Rare Genetic Disorders of Obesity through an in Silico Approach

Abstract: Human melanocortin-4 receptor (hMC4R) mutations have been implicated as the cause for about 6-8% of all severe obesity cases. Drug-like molecules that are able to rescue the functional activity of mutated receptors are highly desirable to combat genetic obesity among this population of patients. One such molecule is the selective MC4R agonist RM-493 (setmelanotide). While this molecule has been shown to activate mutated receptors with 20-fold higher potency over the endogenous agonist, little is known about it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Future studies are warranted to study the therapeutic efficacy of setmelanotide in experimental animal models of MS and whether astrocyte-specific MC4R knockout is able to block these effects. Setmelanotide has shown to be well-tolerated in a phase 2 clinical trial in obese individuals with a rare genetic disorder, and mouse knock-out studies have shown that setmelanotide-associated weight loss is regulated via MC4R, which is mainly attributed to MC4R neurons of the hypothalamus (52, 53). Our findings could set the stage for setmelanotide as a new therapeutic for inflammation associated neurodegeneration in MS.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are warranted to study the therapeutic efficacy of setmelanotide in experimental animal models of MS and whether astrocyte-specific MC4R knockout is able to block these effects. Setmelanotide has shown to be well-tolerated in a phase 2 clinical trial in obese individuals with a rare genetic disorder, and mouse knock-out studies have shown that setmelanotide-associated weight loss is regulated via MC4R, which is mainly attributed to MC4R neurons of the hypothalamus (52, 53). Our findings could set the stage for setmelanotide as a new therapeutic for inflammation associated neurodegeneration in MS.…”
Section: Discussionmentioning
confidence: 99%
“…C3aR1 (NP_033909.1) were based on the structural conserved regions identified from multiple sequence alignment of C3aR1 and C5aR1 across various mammalian species. The approach was based on our earlier approach (Zhang et al, 2005) that has been widely adopted in other GPCR studies (Ahmed et al, 2014; Falls and Zhang, 2018). The sequence alignment used for the homology modeling is shown in the Figure S8.…”
Section: Methodsmentioning
confidence: 99%
“…Although in vitro receptor affinity and activity data show that setmelanotide also exhibits agonist activity at the MC1R, MC3R, and MC5R, much higher concentrations (at least 20‐fold) of setmelanotide are needed for activation of other melanocortin receptors than for MC4R . In 2017, setmelanotide entered phase 3 clinical trials in patients with obesity bearing MC4R mutations . In a phase 2, randomized, double‐blind, placebo‐controlled pilot trial of setmelanotide (NCT02311673), patients with PWS (aged 16‐65 years) treated with the highest dose and for the longest period of time experienced clinically meaningful weight loss despite only modest improvement in hyperphagia .…”
Section: Resultsmentioning
confidence: 99%